Studies of Potency and Efficacy of an Optimized Artemisinin-Quinoline Hybrid against Multiple Stages of the Plasmodium Life Cycle - Helenita C. Quadros; Aysun Çapcı; Lars Herrmann; Sarah D'Alessandro; Diana Fontinha; Raquel Azevedo; Wilmer Villarreal; Nicoletta Basilico; Miguel Prudêncio; Svetlana B. Tsogoeva; Diogo R. M. Moreira (MDPI AG, 2021)
A recently developed artemisinin-quinoline hybrid, named 163A, has been shown to display potent activity against the asexual blood stage of Plasmodium, the malaria parasite. In this study, we determined its in vitro cytotoxicity to mammalian cells, its potency to suppress P. berghei hepatic infection and to decrease the viability of P. falciparum gametocytes, in addition to determining whether the drug exhibits efficacy of a P. berghei infection in mice. This hybrid compound has a low level of cytotoxicity to mammalian cells and, conversely, a high level of selectivity. It is potent in the prevention of hepatic stage development as well as in killing gametocytes, denoting a potential blockage of malaria transmission. The hybrid presents a potent inhibitory activity for beta-hematin crystal formation, in which subsequent assays revealed that its endoperoxide component undergoes bioactivation by reductive reaction with ferrous heme towards the formation of heme-drug adducts; in parallel, the 7-chloroquinoline component has binding affinity for ferric hemin. Both structural components of the hybrid co-operate to enhance the inhibition of beta-hematin, and this bitopic ligand property is essential for arresting the growth of asexual blood parasites. We demonstrated the in vivo efficacy of the hybrid as an erythrocytic schizonticide agent in comparison to a chloroquine/artemisinin combination therapy. Collectively, the findings suggest that the bitopic property of the hybrid is highly operative on heme detoxification suppression, and this provides compelling evidence for explaining the action of the hybrid on the asexual blood stage. For sporozoite and gametocyte stages, the hybrid conserves the potency typically observed for endoperoxide drugs, and this is possibly achieved due to the redox chemistry of endoperoxide components with ferrous heme.